2005
DOI: 10.1002/bjs.4955
|View full text |Cite
|
Sign up to set email alerts
|

Role of liver function tests in predicting common bile duct stones in acute calculous cholecystitis

Abstract: Selection criteria based on GGT can be used in acute calculous cholecystitis to identify high-risk patients who would benefit most from further imaging to exclude choledocholithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 17 publications
9
90
2
5
Order By: Relevance
“…On the other hand, severity of acute cholecystitis also had no significant influence on the level of serum aminotransferases [11] . Jaundice is a common feature of patients with CBD stones [12] .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, severity of acute cholecystitis also had no significant influence on the level of serum aminotransferases [11] . Jaundice is a common feature of patients with CBD stones [12] .…”
Section: Discussionmentioning
confidence: 84%
“…Peng et al [11] documented that the severity of inflammation in cholecystitis with CBD stones did not influence the level of aminotransferases and bilirubin. However, the severity of inflammation was defined as acute attack or not.…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al [64] investigated patients presenting with cholecystitis and found that there was a 33% chance of concomitant CBD stones with a gGT higher than 90 U/l and less than a 2% chance with a gGT lower than 90 U/l. In 1,002 patients undergoing laparoscopic cholecystectomy for any reason, Yang et al [65] observed that abnormal gGT values had a sensitivity of 84.1%, a specificity of 72%, a positive predictive value of 22.4%, and a negative predictive value of 97.9% for detecting concomitant CBD stones before surgery.…”
Section: Endoscopic Sphincterotomy Versus Conservative Managementmentioning
confidence: 99%
“…As a result, the diagnosis of choledocholithiasis by ultrasound and other conventional methods is not particularly reliable. 4,5 Endoscopic retrograde cholangiopancreatography (ERCP) has the highest accuracy in diagnosis of CBD stone. But this approach is invasive, needs expertise, and also expensive.…”
Section: Introductionmentioning
confidence: 99%